Application of impedance technique for study of Ionic conducting properties of lixla1-x TiO3 Perovskite Thin films - Dinh, Nguyen Nang; Ngoc, Nguyen Thi Bao (VNU Journal of Science: Mathematics - Physics, 2006)
Abstract